Edukasi Keluarga Tentang Oralit Dalam Perawatan Diare Pada Anak - Haryani; Zurriyatun Thoyibah; Zuhratul Hajri (J.Abdimas: Community Health, 2021)
Diarrhea is still the biggest cause of death in the world and is a pediatric social problem that often occurs in developing countries, including Indonesia. Diarrhea can cause complications including dehydration, hypovolemic shock, hypokalemia, seizures and malnutrition. The main cause of death from diarrhea in children is dehydration due to lack of electrolytes. Prompt and appropriate handling of diarrheal disease is the key so that infants and toddlers do not experience severe dehydration and cause death. This knowledge is important for mothers and families to have, because toddlers still cannot do everything by themselves. Increased knowledge can be done through education or health counseling. In the Tempit environment, some mothers do not understand how to make Oral Rehydration Solution (ORS) to prevent dehydration. Therefore, it is necessary to do community service in the Tempit Environment, Ampenan Mataram City which is focused on educating families about the importance of fluids and how to make ORS for children with diarrhea. Family education activities consist of identifying the number of families with children under five, health education and evaluation activities. The number of families who participated in community service activities was 20 people. The evaluation of the activities showed that the family had understood how to make a solution of sugar salt and ORS properly and correctly. Education for mothers, families and communities about the importance of fluids and rehydration by making sugar salt solutions and ORS is important carried out continuously, in order to reduce morbidity and mortality in infants and toddlers with diarrhea.